The Influence of Transformational Leadership on Employee Motivation and Performance in the Banking Industry - Oroh, Oliviane; Yusuf Ariyadi, Muhammad; Fauzan Fadlan, A. (International Journal of Management Science and Information Technology, 2024)
This study analyzes the effect of transformational leadership on employee motivation and performance in the banking industry. The research method used is quantitative with a survey approach, involving 200 employees from several leading banks in Indonesia. Data were collected through a questionnaire that measured the respondent's profile, perceptions of transformational leadership, and employee motivation and performance. The results showed that transformational leadership has a significant positive effect on employee motivation and performance. Characteristics of transformational leadership such as charisma, intellectual stimulation, inspirational motivation, and individual consideration increase intrinsic motivation and employee performance. Employees feel appreciated, have challenging tasks, and get significant career development opportunities. This study concludes that transformational leadership can provide a significant competitive advantage for banking companies by increasing employee motivation and performance. Therefore, banking companies are advised to adopt and develop this leadership style in order to achieve long-term success.